2008
DOI: 10.1016/j.jacc.2008.01.076
|View full text |Cite
|
Sign up to set email alerts
|

Provoked Coronary Spasm Predicts Adverse Outcome in Patients With Acute Myocardial Infarction

Abstract: Provoked coronary spasm predicts adverse outcome in AMI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 15 publications
0
31
1
Order By: Relevance
“…[764][765][766][767] Smoking, which exacerbates coronary vasospasm, should be proscribed, and CCBs are first-line therapies 642 ; long-acting nitrates are also effective when combined with CCBs. 755,758 Statins improve endothelium-dependent vasodilation and can be useful in vasospastic angina.…”
Section: December 23/30 2014mentioning
confidence: 99%
“…[764][765][766][767] Smoking, which exacerbates coronary vasospasm, should be proscribed, and CCBs are first-line therapies 642 ; long-acting nitrates are also effective when combined with CCBs. 755,758 Statins improve endothelium-dependent vasodilation and can be useful in vasospastic angina.…”
Section: December 23/30 2014mentioning
confidence: 99%
“…116 Provoked CAS is an independent predictor of major adverse cardiac events. 132 The incidence of recurrent or persistent angina is high in the long term followup of patients with CAS; however, rates of AMI and cardiac mortality are low.…”
Section: Coronary Artery Spasmmentioning
confidence: 99%
“…Wakabayashi et al found that 140 of 240 patients (73%) with acute MI had coronary spasm in the infarct-related arteries or non-infarct-related arteries on acetylcholine provocation at 10-20 days after MI onset, and provoked spasm is 1 of the independent risk factors of MACE including ACS. 25 Another study reported that provoked coronary spasm using ergonovine was closely related to new MI onset and/or progression of coronary atherosclerosis. 26 Among 61 patients with recurrent ACS in the present study, unstable angina caused by coronary spasm was noted in 1 patient with morning onset acute MI and in 1 patient with acute MI onset between 00:00 and 05:59 hours.…”
Section: Clinical Outcome According To Acute MI Onset Timementioning
confidence: 99%